GC-MS Chemical Constituents and in vitro Activities of the Oil Extract of Euryops brevipapposus Leaves used Traditionally for the Management of Some Diseases - Atinuke Adegborioye, Abiodun; Oluwunmi Olaokun, Oyinlola; Chuks Iweriebor, Benson; Chikwulu Obi, Larry (Asian Journal of Chemistry, 2021)
Euryops brevipapposus (Asteraceae) is a medicinal plant of a local community utilized traditionally for its recognized effectiveness in managing non-communicable diseases, especially asthma. The traditional use of E. brevipapposus lacks scientific evidence and the increased burden of asthma makes confirming this claim paramount. The study characterized by GC-MS the bioactive compounds of E. brevipapposus essential oil (EbO) extracted with Clevenger apparatus. The antibacterial efficacy and antioxidant activity by free radical scavenging ability were investigated in vitro using standard methods. A strong antioxidant IC50 value of 6.71 × 10-7 mg/mL of oil was obtained for DPPH. The antibacterial activity against Escherichia coli and Vibrio spp. (MIC value of 0.055 mg/mL) was superior. GC-MS analysis of EbO showed α-phellandrene, α-pinene, germacrene D, β-pinene, β-mycrene, (E)-β-ocimene and bicyclogermacrene as the major compounds. The antioxidant and antibacterial potentials of E. brevipapposus may justify the therapeutic claims and local usage of this plant.